Modeling Influencing Factors in B-Cell Reconstitution After Hematopoietic Stem Cell Transplantation in Children - van der Maas, Nicolaas G.; von Asmuth, Erik G. J.; Berghuis, Dagmar; van Schouwenburg, Pauline A.; Putter, Hein; van der Burg, Mirjam; Lankester, Arjan C. (Frontiers in Immunology, 2021)
Reduced total and memory B-cell numbers in peripheral blood long term after hematopoietic stem cell transplantation (HSCT) are associated with an increased incidence of infections and immune complications. Using novel modelling strategies, baseline factors influencing B-cell reconstitution can be comprehensively studied. This study aims to investigate the numerical total and memory B-cell reconstitution in children and the association with baseline determinants 0.5-2 years after allogeneic HSCT. Eligible for inclusion were children transplanted in our center between 2004-2017 who received a first HSCT for malignant or non-malignant disorders. The continuous absolute counts of total and memory B-cells were evaluated as outcome measure. Exploratory analysis at one year was done to identify possible determinants. Linear mixed effect modelling was used to analyze the association of these determinants with total and memory B-cell reconstitution 0.5-2 years after HSCT. In a cohort of 223 evaluable patients analyzed at 1-year after HSCT donor age, stem cell source, donor type, recipient age and conditioning were identified as significant determinants for total and memory B-cell numbers. Multivariable analysis revealed that both donor and recipient age were inversely correlated with the size of total and memory B-cell reconstitution. In contrast, no correlation was found with stem cell source, donor type and conditioning. Making use of linear mixed modelling both stem cell donor and recipient age were identified as independent determinants of total and memory B-cell reconstitution 0.5-2 years after HSCT.